PTH-141 The long term use of botulinum toxin in patients with recurrent acute pancreatitis. (17th June 2017) - Sanders, J; White, L; Hilal, M Abu; Hamady, Z; Johnson, C; Shek, F
Abstract : Introduction: Patients with recurrent acute pancreatitis suffers from repeated attacks of acute pancreatitis. They are frequently admitted to hospital with abdominal pain. They undergo numerous investigations for the cause of the pancreatitis. Botulinum toxin has been used to treat patients with sphincter of oddi dysfunction 1 but as yet there are no long term data of the use of botulinum toxin in patients with recurrent acute pancreatitis. Method: Data collection for this series of patients started in 2011. Patients were fully consented for a duodenoscopy and a botulinum toxin injection to the sphincter of oddi. Using a duodenoscope (Olympus TJF-260V) to identify the papilla of vater, 100 units of botulinum toxin is injected to the sphincter of oddi. Patients with pancreatic divisum were injected with 100units of botulinum toxin to both papillae respectively. Patients were given a pre and post (14 days after)-procedure quality of life questionnaire (QLQ-C30-PAN26- specific for pancreatic diseases) and patients were asked to fill in the questionnaires and post back to the department of Endoscopy. The quality of life score ranged from 1–4. Patients were reviewed in clinic post procedure and were offered a repeat procedure when appropriate. Results: 21 patients (12 female:9 male) with recurrent acute pancreatitis were treated with botulinum toxin injection to the sphincter of oddi. 2 patients were known to have pancreatic divisum. The rest did not have a known cause for their pancreatitis. The mean age were 35 (Range 21–75). The mean improvement in the quality of life score in a sample of 12 patients was 16.5 (range 6–36). The response rate was 57%. No complications were noted during this period of study. Conclusion: This study demonstrates that long term use of Botulinum toxin in patients with recurrent acute pancreatitis is a safe and effective way to manage these patients. This treatment can also be the treatment of choice rather than the pancreatic sphincterotomy which carries high morbidity of post ERCP pancreatitis. Reference: . Wehrmann T, Schmitt TH, Arndt A, Lembcke B, Caspary WF, Seifert H. Endoscopic injection of botulinum toxin in patients with recurrent acute pancreatitis due to pancreatic sphincter of Oddi dysfunction. Aliment Pharmacol Ther. 2000Nov;14(11):1469–77. Disclosure of Interest: None Declared